Productivity gaps and global systematic risk exposure: pricing country-industry portfolios - Anand, Punit; Balvers, Ronald J.; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2020)
Shocks transmitted from productivity leaders to lagging economies are systematic sources of risk. Global technology and knowledge diffusion leads to predictable patterns in productivity dynamics across countries and industries. Technology gaps determine the level of exposure to the systematic productivity shocks. Firms in a country-industry with larger technology gaps relative to the world leader are more dependent on the leader’s innovations compared to their own productivity improvements. They thus have higher loadings on the leader productivity shocks and higher average stock returns. For OECD panel data, a country-industry’s technology gap significantly predicts the stock returns of the country-industry: holding the quintile of country-industry portfolios with the largest gaps and shorting the quintile with the smallest gaps generates annual returns of 9.8% (6.7% after risk adjustment with standard factors). A factor representing the technological productivity gap explains country-industry portfolio returns substantially better than standard factor models. Loadings on leader-country productivity shocks have substantial correlation with technology gaps, and leader productivity shocks are more important for stock returns than idiosyncratic productivity shocks. These findings support that the technology gaps and associated higher average returns are indeed linked to systematic risk. Valuation Insight: Firm in economies that lag technologically have a value-enhancing potential for productivity improvement due to spillovers from technology leaders. However, this potential has the drawback that the firm value becomes riskier: the firm is more sensitive to the systematic innovation risk that is integral to technology leaders.
74 p. ; Includes bibliographical references (pp. 36-40) ; November 3, 2020.
Keywords: Production-based asset pricing; Productivity gap; Total factor productivity; OECD countries; International equity returns; Technology diffusion